Titanium and copper oxide based catalysts for the in-situ reactions of methanation and desulfurization in the removal of sour gases from simulated natural gas - Wan Azelee, Wan Abu Bakar (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2009)
The objective of this novel catalyst development is to achieve both low temperature and high conversion of sour gases. Supported mixed metal oxide catalysts were prepared by impregnating the catalysts on alumina beads for the in-situ reactions of H2S desulfurization and CO2 methanation from room temperature up to 200oC. The results showed that the 100% conversion of H2S to elemental sulfur for all of the potential catalysts was achieved at 100oC. However, methanation of CO2 in the presence of H2S yielded 0.4% CH4 over Fe/ Zn/ Cu/ Ti-Al2O3 catalyst and 0.7% CH4 over Fe/ Zn/ Cu-Al2O3 catalyst at maximum studied temperature of 200oC. XPS results indicated that spinel compounds of CuFe2O4 and Fe3O4 act as the active sites on the Fe/ Zn/ Cu-Al2O3 and Fe/ Zn/ Cu/ Ti-Al2O3 catalysts. The appearance of Fe3+-OH on Fe/ Zn/ Cu/ Ti-Al2O3 catalyst increased its H2S desulfurization activity. N2 adsorption-desorption analysis illustrated that 34% of the surface area of Fe/ Zn/ Cu-Al2O3 catalyst was reduced while Fe/ Zn/ Cu/ Ti-Al2O3 catalyst showed reduction of 17% after catalytic testing, which indicated the deactivation of the catalysts resulted from sulfur poisoning